ASSESSMENT OF FEASIBILITY AND COMPLICATIONS OF LAPAROSCOPIC CHOLECYSTECTOMY IN CIRRHOTIC PATIENTS - Goyal, Nitin; Pandey, Anshuman; Masood, Shakeel; Chauhan, Smita; Gupta, Alankar; Noman, Khalid (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Abstract : Introduction: From the era of absolute contraindication to the phase of preferred treatment, the technique of laparoscopic cholecystectomy advances with time. Here, we report our experience of laparoscopic cholecystectomy in 20 patients of liver cirrhosis. In our institute, laparoscopic cholecystectomy is the preferred choice for cholelithiasis in cirrhotic patient. Methods: In last 2 years, 180 laparoscopic cholecystectomies were performed and 20 patients were cirrhotic. Their data analyzed retrospectively in terms of preoperative optimization, operative technique and results. Results: Laparoscopic cholecystectomy was completed successfully in 19 patients and one was converted to open. Mean operative time was 54 minutes. No additional port was required in all cases. Calot's first dissection was performed in 18 patients and fundus first technique was used in 2 patients due to unclear anatomy. Liver bed bleeding was present in 16 patients, which was controlled effectively. Subhepatic drain was placed in 12 patients. There was no mortality. MorbidityÂ  in two patients was worsening of ascites in one; and incisional hernia in other patient which was converted to open. Port site complications were not noted in any patient and there was no evidence of intraabdominal bleeding or bile leak postoperatively. Blood and component transfusion was required in 2 patients. Average length of hospital stay was 4.8 days. Conclusion: Though laparoscopic cholecystectomy may be difficult in cirrhotic patients but it is feasible and relatively safe. It offers many advantages in cirrhotic patients and associated with low morbidity when compared with open surgery. Keywords: cirrhosis, laparoscopic cholecystectomy, difficult cholecystectomy